Low Frequency Forced Oscillation Lung Function Test Can Distinguish Dynamic Tissue Non-linearity in COPD Patients - Ghita, Maria; Copot, Dana; Ghita, Mihaela; Derom, Eric; Ionescu, Clara (Frontiers in Physiology, 2019)
This paper introduces the use of low frequencies forced oscillation technique (FOT) in the presence of breathing signal. The hypothesis tested is to evaluate the sensitivity of FOT to various degrees of obstruction in COPD patients. The use of FOT to evaluate respiratory impedance has been broadly recognized and its complementary use next to standardized method as spirometry and body plethysmography has been well documented. Typical use of FOT uses frequencies between 4-32 Hz and above. However, interesting information at frequencies below 4 Hz is related to viscoelastic properties of parenchyma. Structural changes in COPD affect viscoelastic properties and we propose to investigate the use of FOT at low frequencies with a fourth generation fan-based FOT device. The generator nonlinearity introduced by the device is separated from the linear approximation of the impedance before evaluating the results on patients. Three groups of COPD obstruction, GOLD II, III and IV are evaluated. We found significant differences in mechanical parameters (tissue damping, tissue elasticity, histeresivity) and increased degrees of nonlinear dynamic contributions in the impedance data with increasing degree of obstruction (p 0:01). The results obtained suggest that our propsoed index for nonlinearity evaluation correlates better with degrees of heterogeneity linked to COPD GOLD stages, than the currently used histeresivity index. The protocol and method may prove useful to improve current diagnosis percentages for various COPD phenotypes.